Left-ventricular innervation assessed by 123I-SPECT/CT is associated with cardiac events in inherited arrhythmia syndromes. (1st August 2020) - Siebermair, Johannes; Lehner, Sebastian; Sattler, Stefan M.; Rizas, Konstantinos D.; Beckmann, Britt-Maria; Becker, Alexander; Schiller, Julia; Metz, Corona; Zacherl, Mathias; Vonderlin, Nadine; Rassaf, Tienush; Dobrev, Dobromir; et al.
Abstract: Aims: Impaired myocardial sympathetic innervation assessed by 123 Iodine-Metaiodobenzylguanidine ( 123 I-MIBG) scintigraphy is associated with cardiac events. Since regional disparities of structural abnormalities are common in inherited arrhythmia syndromes (iAS), a chamber-specific innervation assessment of the right (RV) and left ventricle (LV) could provide important insights for a patient-individual therapy. Aim of this study was to evaluate chamber-specific patterns of autonomic innervation by Single-photon emission computed tomography/computed tomography (SPECT/CT) in patients with iAS with respect to clinical outcome regarding cardiac events. Methods and results: We assessed ventricular sympathetic innervation (LV, RV and planar heart/mediastinum-ratios, and washout-rates) by 123 I-MIBG-SPECT/CT in 48 patients (arrhythmogenic right ventricular cardiomyopathy [ARVC], n = 26; laminopathy, n = 8; idiopathic ventricular fibrillation [iVF], n = 14) in relation to a composite clinical endpoint (ventricular arrhythmia; cardiac death; cardiac hospitalization). RV tracer uptake was lower in patients with ARVC than in laminopathy and iVF patients (1.7 ± 0.4 vs. 2.1 ± 0.7 and 2.1 ± 0.5, respectively). Over a median follow-up of 2.2 years, the combined endpoint was met in 18 patients (n = 12 ventricular tachyarrhythmias, n = 5 hospitalizations, n = 1 death). LV, but not RV H/M ratio was associated with the combined endpoint (hazard-ratio 2.82 [1.30–6.10], p < 0.01). After adjustment for LV and RV function, LV H/M-ratio still remained a significant predictor for cardiac events (hazard-ratio 2.79 [1.06–7.35], p = 0.04). Conclusion: We demonstrated that chamber-specific 123 MIBG-SPECT/CT imaging is feasible and that reduced LV sympathetic innervation was associated with worse outcome in iAS. These findings provide novel insights into the potential role of regional autonomic nervous system heterogeneity for the evolution of life-threatening cardiac events in iAS. Highlights: 123 I-MIBG SPECT/CT allows for chamber-specific sympathetic innervation assessment. Impaired LV innervation associated with worse outcome in inherited arrhythmias. Potential role of LV innervation assessment for risk stratification in iAS.